1993
DOI: 10.1063/1.353055
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically driven alloying and grain size changes in nanocrystalline Fe-Cu powders

Abstract: Highly supersaturated nanocrystalline Fe,Culcc-X alloys (lO Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
121
1
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(134 citation statements)
references
References 29 publications
10
121
1
2
Order By: Relevance
“…The coexistence of FCC and BCC has been seen in the system Fe-Cu and was explained by an enhanced solubility due to the high dislocation density [45] but this explanation may not be applicable in the present case. From Rietveld refinement it was determined that the crystallite size of the BCC phase goes from 44 nm before milling to 2 nm after 80 h of milling.…”
Section: Ti-based Bccmentioning
confidence: 61%
“…The coexistence of FCC and BCC has been seen in the system Fe-Cu and was explained by an enhanced solubility due to the high dislocation density [45] but this explanation may not be applicable in the present case. From Rietveld refinement it was determined that the crystallite size of the BCC phase goes from 44 nm before milling to 2 nm after 80 h of milling.…”
Section: Ti-based Bccmentioning
confidence: 61%
“…34) Due to this kinetic advantage, a filament with sharp tips would sphereodize rather than dissolve, as observed in many experiments. Schwarz 35) (and Eckert et al, 3,4,7) to some extent) has suggested mechanisms based on interactions between the dislocation strain fields and the solutes. They hypothesized preferential segregation of solute atoms into core regions of dislocations, which are abundant in SPD materials.…”
Section: Mechanisms Of Driven Alloying and Uphill Interdiffusionmentioning
confidence: 99%
“…In other words, the externally imposed randomizing action forces the issue despite the fact that the two species dislike each other. The typical deformation routes used were ball milling of powder mixtures, [3][4][5][6][7][8][9][10][11][12][13] cold rolling of stacked multilayers, 14) extrusion of in situ composites, 15) and high pressure torsion. 16) Studies of deformation-driven alloying overcoming thermodynamic driving forces are motivated not only by the science appeal of this fundamental subject, but also by the unusual properties resulting from the nonequilibrium alloys created.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly known that during MA, powders undergo a severe plastic deformation, which introduces a number of defects into the material, and it is worth noting that this causes a gradual change in the state of the powder mixtures and hence their properties [8,9]. Further, Eckert et al [10] found that the final grain size is determined by the competition between the deformation produced by a milling process, and the dynamic recovery in the milled material. On the other hand, it has been suggested that the stacking fault energy (SFE) has a strong influence on the evolution of the dislocation structure, which precedes and results in the nanocrystalline structure formation [11].…”
Section: Introductionmentioning
confidence: 99%